Late-onset familial amyloidosis polyneuropathy associated with c.186G>C in transthyretin - Eugenia Conti; Sebastián Menazzi; Ana Mariel Finkelsteyn; María de Lourdes Figuerola (Revista de la Facultad de Ciencias Médicas de Córdoba, 2024)
Introduction: The most common form of hereditary amyloidosis is associated with variants of transthyretin (TTR). Familial amyloidosis polyneuropathy associated with variants of TTR (FAP-TTR) is an infrequent, multisystemic disease, with predominant involvement of the peripheral nervous system. More than 130 pathogenic variants have been identified so far and most of them are amyloidogenic, being Val30Met the most frequently described. Case report: A 74 year-old male was evaluated for progressive decreased sensitivity and associated loss of strength in four limbs in the previous two years, needing assistance for walking. Areflexia, bilateral tibialis anterior and gastrocnemius atrophy, bilateral anesthesia and apalesthesia were found in lower limbs. Bilateral hypoesthesia was reported in upper limbs. No painful dysesthesia, hyperalgesia or allodynia were found. DNA sequencing of the TTR gene led to the detection of the variant c.186G>C in heterozygous state. The resulting variant (Glu62Asp), located in the critical functional domain, has not been published before. Conclusion: The importance of considering late onset, sporadic FAP-TTR as a differential diagnosis of cryptogenic polyneuropathy is highlighted.